Basic research public procurement: the impact on supplier companies. Issue 3 (2nd September 2019) - Dal Molin, Martina; Previtali, Ezio
Abstract : Purpose: The purpose of this paper is to estimate and assess the impact of public procurement activities of an Italian basic research center (the National Institute for Nuclear Physics [INFN]) on supplier companies. Design/methodology/approach: Starting from the exploratory nature of this research, a single case study research strategy has been applied. The impact of basic research public procurement has been estimated using survey data on 168 INFN supplier companies. Supplier companies have been surveyed on six different categories of company outcomes, namely, sales volume, learning and innovation, relationship with the market, alliances and network and social impact. Findings: Results of the analysis reported that the activity of INFN public procurement generates a positive impact on supplier companies on different dimensions, especially related to learning and innovative outcome and economic impact and market penetration outcome. Social implications: Policy implications can be derived from the current study. In particular, to support the policymakers in the effort of assessing the impact of basic research public procurement, this study, first highlights the impact dimensions on supplier companies, and second, it provides empirical evidence of public procurement as a viable tool to foster companies' innovation. Originality/value: This research explores a relevant but understudied topic that has recently attracted the attention of policymakers. In fact, although public procurement have been recognized as a tool to foster companies' innovation, empirical evidence is still scant, particularly in the case of basic research.